METODE PENDIDIKAN DALAM AL-QUR’AN (KAJIAN TAFSIR TEMATIK) - Ahmad Syaifulloh (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2018)
As a component of science, the method can deliver an educational process can achieve their education goal quickly and precisely. This will happen when the methods of education and teaching which is in line with the substance and purpose. Therefore an educator must master many learning methods, so that he can choose the method that is appropriate to the circumstances. In the world of Islamic education, learning and educational goals let in accordance with the Koran and the Hadith as the source of the basic teachings of Islam. In the two sources of the law there had to be a strong foundation on educational methods, as has been done by the Prophet Muhammad in preaching and educating Muslims. Through the study of thematic interpretation (Tafsir thematic), this study aims to uncover methods of education contained in the Koran, as well as explore the hadiths relevant to such methods. The results of this study indicate that there are several methods of education in the Quran include: storytelling (Hud : 120), and answer method (Al-Baqarah : 189), the method of wisdom, advice, discussion (An- Nahl : 125), and the method of demonstration (al-Kahf : 77).